The Effects Of Telecommunication Technology And Leadership Quality On Private Consumption Spending In Malaysia - Lim, Yu Syuen (2023)
Private consumption is one of the major players in generating Malaysia’s economic growth as it constitutes over 60 per cent of national income. As such, comprehending this primary domestic growth engine is crucial, particularly in light of the evolving landscape affected by COVID-19 and shifting consumption behaviours. In contrast to the previous literature on private consumption, this study delves into non-economic factors, specifically examining the impact of telecommunication technology and national leadership quality on private consumption in Malaysia from 1990:Q1 to 2020:Q4.